Diametaphyseal Distal Forearm Fractures in Children: A STROBE Compliant Comparison of Outcomes of Different Stabilization Techniques Regarding Complications - Andreas D. P. Wollkopf; Florian S. Halbeisen; Stefan G. Holland-Cunz; Johannes Mayr (MDPI AG, 2023)
Diametaphyseal forearm fractures are difficult to treat because standard methods for long-bone fracture stabilization in the metaphyseal or diaphyseal regions are less effective in this transition zone. We hypothesized that there is no difference in outcomes between conservative and surgical treatment of diametaphyseal forearm fractures. This retrospective analysis included 132 patients who had undergone treatment for diametaphyseal forearm fracture between 2013 and 2020 at our institution. The primary analysis compared complications occurring in patients treated conservatively with those occurring in patients managed surgically (ESIN, K-wire fixation, KESIN stabilization, or open reduction and plate osteosynthesis). In a subgroup analysis, we compared the two most frequently applied surgical stabilization techniques in distal forearm fractures (i.e., ESIN and K-wire) with conservative treatment. The mean age of the patients at the time of intervention was 9.43 ± 3.78 years (mean ± SD). Most patients were male (91; 68.9%), and 70 of 132 (53.1%) patients underwent surgical stabilization. The rate of re-intervention or complications was similar after conservative and surgical treatment, and ESIN or K-wire fixation achieved comparable complication rates. Recurrent displacement of fragments was the most frequent reason for re-interventions (13 of 15 patients; 86.6%). There was no permanent damage as a result of a complication. The median time of exposure to image intensifier radiation was comparable between ESIN (95.5 s) and K-wire fixation (85.0 s), but significantly lower during conservative treatment (15.0 s; p = 0.001).